Föderalismus-Rhetorik-Dekonstruktionen - Rechtsdogmatik als Literaturdogmatik : Instrumentalföderalismus in den Vereinigten Staaten von Amerika und in der Bundesrepublik Deutschland als romantisch-lyrische Lesekonvention vor Gericht - Neugärtner, Rico David, 1989- (Sprache und Medialität des Rechts ;, 2023)
»Deconstructing the Rhetoric of Federalism - On Doctrine in Law and Literature. Instrumental Federalism in the United States of America and the Federal Republic of Germany as a Lyrical Figure of Reading«: In American and German federalism, courts assertively deploy topoi such as ›state dignity‹ or ›Bundestreu‹' which are not laid down in the constitutional texts. The comparative study scrutinizes these ›unwritten‹ doctrines as examples of activist judicial constitutionalism. The topoi revolve around anthropomorphic, ›lyrical‹ notions of ›dignity‹ and ›fidelity‹. Building on deconstruction in literary criticism, the book analyzes the force of anthropomorphic doctrine in law and literature.